Thoracic Spinal Anesthesia (TSA) in Patients with Congestive Heart Failure and Pleural Effusion Undergoing Breast Tumor Surgery: A Case Report - Wiedjaja, Aryasena Andhika; Rizqhan, Muhammad (Perhimpunan Dokter Spesialis Anestesiologi dan Terapi Intensif, 2025)
Background: Thoracic spinal anesthesia (TSA) is a regional anesthesia technique that can serve as an alternative to general anesthesia, particularly for patients with cardiovascular and respiratory comorbidities, to reduce adverse effects and provide a more effective procedure.Case: A 55-year-old female patient with a left breast tumor and comorbidities including uncontrolled hypertension and type 2 diabetes mellitus, as well as congestive heart failure (CHF) and bilateral pleural effusion, scheduled for lumpectomy by a surgical specialist. The preoperative assessment showed stable hemodynamics with no significant changes in laboratory results. The patient received hyperbaric bupivacaine 5 mg (1cc), fentanyl 25 mcg (0.5cc), and an adjuvant of dexamethasone 5 mg (1cc) for the TSA procedure at the T4-T5 level. Intraoperatively, there were no significant hemodynamic changes, and postoperatively, the patient had a good recovery and mobilization.Discussion: The TSA procedure is an alternative anesthesia technique when patients undergoing general anesthesia have a high risk of morbidity and mortality, especially in geriatric patients with physiological body disorders and multiple comorbidities. TSA has been increasingly used as a safe anesthesia technique, capable of accelerating recovery time, minimizing side effects, and providing better outcomes in terms of perioperative morbidity and mortality compared to general anesthesia. The current limitations of the literature regarding TSA include the lack of large-scale studies, the absence of standardized protocols for TSA, a focus on specific surgeries only, and concerns about the safety of this procedure.Conclusion: The TSA can be used as a regional anesthesia procedure for patients undergoing breast tumor surgery. TSA has a simple technique and is efficient in providing sensory and motor blockade.